"I'm just trying to cope for both of us": Challenges and supports of family caregivers in participant-directed programs. Issue 2 (17th February 2019) - Milliken, Aimee; Mahoney, Ellen K.; Mahoney, Kevin J.; Mignosa, Kate; Rodriguez, Isabella; Cuchetti, Catherine; Inoue, Megumi
ABSTRACT: Recently, national attention has focused on the needs of family caregivers providing complex chronic care, noting the necessity to better understand the scope of challenges they encounter. Although a robust body of literature exists about the scope of family caregiving, little is known specifically about the experiences and perspectives of family caregivers who support participant directed (PD) participants, particularly across the caregiving trajectory. Therefore, the aim of this qualitative descriptive study was to describe what family caregivers of individuals with developmental disabilities, physical disabilities, aging, or chronic health conditions identify as the challenges they experience as complex, and their perceptions of the effectiveness and gaps in family support resources in PD. Semi-structured interviews were audio-recorded with a purposive sample of caregivers. Transcribed interviews were analyzed using conventional content analysis. Fifty-four caregivers of individuals with a range of disabilities participated (age 34–78, M 59.9 ± 8.8; male 19%; spouse 17%, parent 61%). Six categories emerged from the analysis: contextualizing complexity, complexity in transitions, coping with complexity: advocacy & isolation, supportive support, unsupportive support, and systems challenges. Caregivers emphasized the interplay between unpredictability, transitions, and complexity and the interaction between the person receiving support, the caregiver's own situation, and the environment. Findings highlight the need, and provide a guide, for family assessment and for tailoring interventions matched to the profiles and self-identified challenges of families living with disability. Social workers can learn what families see as complex and what support broker behaviors families find helpful, and which not.